Begin boldly : how women can reimagine risk, embrace uncertainty, and launch a brilliant career - Arscott, Christie Hunter (Berrett-Koehler Publishers, Inc., 2022)
"Too often, women hesitate to take career risks due to systemic workplace inequity. This book teaches women how to take the right risks for lasting career success. Many women enter the workforce feeling like they can never make a mistake, and as a result, they don't take risks in the crucial early stages of their careers. Women, and BIPOC women especially, are disproportionally penalized for mistakes, so any risk begins to feel like a bad risk. A 2019 KPMG study found that fewer than 43 percent of women surveyed were willing to take "big" risks, including volunteering to do a major presentation or asking for a pay raise. Christie Hunter Arscott equips readers with the ability to differentiate between reckless and intelligent risks using an actionable model built around three mindsets: a curious mindset, a courageous mindset, and an agile mindset. With a step-by-step method for taking risks, making refinements, and assessing rewards, Arscott's approach gives women a flexible and repeatable framework to guide them through this critical career skill. Liftoff empowers women to take chances on themselves so that risk-taking becomes an enlightening and empowering antidote for self-doubt. This book will include a discussion guide"--